Strategies of Communicative Arabic Language Mastery Based on Lughawiyyah at Ma’had Umar Bin Al-Khattab Surabaya - Luthfi Ans; Nurdyansyah Nurdyansyah; Eni Fariyatul Fahyuni (International Consortium of Education and Culture Research Studies, 2020)
Arabic language is often taught by Arabic educational institutions only as a tool to read religious texts, not as the function of language is to communicate. The purpose of this research is to show a new strategy of mastering comprehensive communicative Arabic language based on 4 language skills (maharat lughawiyyah), namely listening, speaking, reading, and writing integrally and not separately. This study uses descriptive qualitative methods, data collection is carried out through observation and interviews. The results of this study indicate weak language skills due to partial mastery strategies in Arabic. The conclusion of this study shows that the ability to communicate Arabic must be built on 4 language skills simultaneously, related, intact, integrated and not fragmented.